PERANAN PENYULUH PERTANIAN DALAM MENINGKATKAN KINERJA KELEMBAGAAN KELOMPOK TANI PADI SAWAH PENERIMA BANTUAN RICE MILLING UNIT (RMU) DI KOTA BANDAR LAMPUNG - Flora Defika; Irwan Efendi; Kordiyana K Rangga (Journal of Food System & Agribusiness, 2021)
This study aims to analyze: 1) the level of the role of agricultural agents; 2) the level of institutional performance of farmer groups; 3) the relationship between the level of the role of agricultural extension agents and the institutional performance of rice farmer groups in the use of RMU in Bandar Lampung City. This research was conducted in the city of Bandar Lampung with 56 farmer respondents. Methods of data collection using a survey method, with descriptive analysis and using a non-parametric rank spearman correlation statistical test to test the hypothesis. The results showed that the role of agricultural extension agents in improving the institutionalization of rice farmer groups receiving RMU assistance was in the medium category, the institutional level of farmer groups in the use of RMU was in the medium category, and the role of agricultural instructors had a significant relationship with the institutional performance of farmer groups.